Anti-inflammatory and anti-pyretic effects of hexane fraction of Ardisia crispa Thunb. D.C - Lau, Moi Fong; Abd Hamid @ Abdul Razak, Roslida; Sukardi, Sabrina; Somchit, M. Nhareet (Società Italo-Latinoamericana di Etnomedicina, 2009)
Hexane fraction of Ardisia crispa root (ACHE) was used to investigate its anti-inflammatory and anti-pyretic activities in this study. For anti-inflammatory activity, 12-O-tetradecanoylphorbol-13-acetate (TPA) was applied to ear of mice to induce oedema and treated with 0.5,1 and 2mg/ear of ACHE topically. In cotton-pellet granuloma test, treated groups have received 3, 10, 30 and 100mg/kg of hexane extract administered orally for 7 days. For antipyretic activity, brewer's yeast was injected in mice to induce fever and later, ACHE at dose ranging from 10 to 300 mg/kg were administered to the rats orally. The results exhibited that 1 and 2mg/ear of ACHE produced significant suppression by 19.9% and 20.2% respectively. the lowest dose of ACHE showed no significant effect when compared with control. Results showed that ACHE showed significant anti-pyretic effect at all doses (10, 30, 100 and 300 mg/kg). At 30, 100 and 300mg/kg, ACHE even exhibited higher efficacy when compared with 100 mg/kg acetaminophen. ACHE also elicited a significant (P<0.05) inhibition of granuloma tissue and exudate formation. Thus, it can be concluded that Ardisia crispa posseses antiinflammatory and antipyretic effects.